Promoting Critical Thinking Skills through History Research in the Classroom: An Innovation in Character Education - Roro Wilis; Dyah Kumalasari; Nendri Hapsari (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
This study aims to explore the implementation of a history research class at SMA Negeri 9 Yogyakarta that utilizes the development of critical thinking skills to build student character. This research uses a qualitative method with a case study at SMA Negeri 9 Yogyakarta. Data collection techniques were conducted through interviews, observations, and document analysis. Sampling was done by purposive sampling involving subjects such as history teachers and some grade X students; then analyzed using the interactive model data triangulation technique. The results showed that the systematic implementation of history research classes was intended to provide students with a deeper understanding in a practical way. In addition to introducing regional identity, the use of local history of Yogyakarta Special Region as a learning resource can also accelerate knowledge transfer. Interestingly, history teachers at SMA Negeri 9 Yogyakarta try to update Kuntowijoyo's research method by presenting digital sources to reconstruct historical events. In addition to fulfilling the six indicators of critical thinking skills, the implementation of history research classes also internalizes character education. This research implies that the development of critical thinking skills in history learning has a positive impact on student character building. The results of this study can be useful as an alternative reference regarding the history learning model.